Size-resolved airborne particle control in a dental operatory: field comparison of window opening, portable air purifier, and UV air disinfection - Chen Chen; Di Zhang; Xiaoyi Xiao; Chuanhao Wang; Ruixin Nie; Xiaojing Lin; Mengmeng Cao; Meiqiu Hong; Yanjun Su; Bin Zhao; Shanshan Shi; Mingyao Yao; et al. (Building and Environment, 2026)

MEHP exposure disrupts the self-renewal and differentiation of GC-1 cells by up-regulating m6A levels, leading to reproductive damage in immature rats - Yanjun Ding; Xiazhu Zhou; Yifan Hong; Jing Chen; Haohui Tang; Binrong Sun; Chunlan Long; Lianju Shen; Shengde Wu; Yuexin Wei; Guanghui Wei (Toxicology, 2026)

Harnessing Lactiplantibacillus plantarum LW11: A promising bio-preservative for extending cake shelf life through antifungal metabolites - Xuechun Wang; Zhishuo Zhang; Cuihua Chang; Yujie Su; Luping Gu; Yanjun Yang; Hong Sun; Junhua Li (Food Control, 2026)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

Different responses of soil bacterial necromass carbon and fungal necromass carbon to nitrogen deposition in meadow steppe - Na Jiang; Hao Zhang; Siyu Zhang; Jie Qin; Hui Wang; Yanjun Zhang; Dianlin Yang; Lili Wang; Qiannan Yang; He Ye; Mei Hong; Haifang Zhang (Applied Soil Ecology, 2025)

Synergistic nano-bioeffects: Dual impact of bisphenol-derived carbon dots on environmental health and antimicrobial therapy - Siyuan Hu; Xinzhong Zhang; Jiayu Li; Xiang Wang; Chen Gao; Jiatong Zhou; Jing Cai; Miaomiao Yin; Rufang Zhao; Xin Ding; Wei Hong; Yanjun Hu (Chemical Engineering Journal, 2025)

De novo design of dual-detection fluorescent sensors for bisulfite and copper (II) ion based on cascade activation - Tian Tan; Wenyu Xi; Chenxu Duan; Ying Han; Peikun Xiao; Hongqi Yin; Hong Huang; Xulang Chen; Yanjun Hu; Xiaohuan Huang (Analytica Chimica Acta, 2025)

Actinobacteria derived from soybean/corn intercropping influence the subsequent wheat - Songhe Chen; Ruirui Li; Bo Lv; Yanjun Li; Junda Li; Mengzhen Zhang; Xiaoxiao Ma; Cunhu Wang; Ruineng Xu; Yonghong Wang; Hong Liao; Yongjia Zhong (Agriculture, Ecosystems & Environment, 2025)

Emerging role of adaptive immunity in diabetes-induced cognitive impairment: from the periphery to the brain - Genhui Yang; Runtao Su; Jie Bu; Ying Li; Xueling Lin; Jiahui Jin; Yanjun Zhang; Pengwei Zhuang; Hong Guo; Qingsheng Yin (Metabolic Brain Disease, 2025)

Rigid polymethacrylimide composites foam for efficient electromagnetic dissipation and infrared stealth - Zihang Zhang; Zixuan Wang; Yanjun Zhang; Peiyuan Zou; Mingyang Zhu; Shuangshuang Li; Xinwei Tang; Yezi Lu; Wei Li; Kaixin Lai; Wei Hong; Yufei Li; et al. (Chemical Engineering Journal, 2025)

Impact of urbanized atmosphere-land processing to the near-ground distribution of air pollution over Central Liaoning Urban Agglomeration - Wenxi Zhang; Zhenxin Liu; Xiaolan Li; Yuhao Mao; Yanjun Ma; Hong Liao (Atmospheric Environment, 2024)

Differential expression of TOR complex 1 components in Colletotrichum camelliae isolates confers natural resistance to rapamycin - Yuanye Zhu; Yanjun Li; Hong Liu; He Li (Pesticide Biochemistry and Physiology, 2024)

Cobalt single-site molecular Catalyst-mediated electrochemical Hydrodechlorination for detoxification of halogenated Antibiotics: Performance, reaction pathway and mechanism - Yinan Liu; Xiangyi Tang; Fei Shen; Jiahong Zou; Yanjun Yin; Zhaojie Jiao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Guangming Jiang; Hong Liu (Chemical Engineering Journal, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

National-scale Geochemical Survey: Distribution of chemical elements in stream sediment of South and Central Asia - Jun Hong; Guanglu Meng; Jing Zhang; Jifei Cao; Bin Wang; Yanjun Luo; Bo Yang; Xueqi Zhang; Domenico Cicchella (Journal of Geochemical Exploration, 2024)

Decoding PFAS contamination via Raman spectroscopy: A combined DFT and machine learning investigation - Yangxiu Chen; Yanjun Yang; Jiaheng Cui; Hong Zhang; Yiping Zhao (Journal of Hazardous Materials, 2024)

Fine-tuning bromide AIE probes for Hg2+ detection in mitochondria with wash-free staining - Tian Tan; Chuang Zhang; Ying Han; Ruijun Chu; Wenyu Xi; Xulang Chen; Jingyu Sun; Hong Huang; Yanjun Hu; Xiaohuan Huang (Journal of Hazardous Materials, 2024)

Enhancing column bioleaching of chalcocite by isolated iron metabolism partners Leptospirillum ferriphilum/Acidiphilium sp. coupling with systematically utilizing cellulosic waste - Xingyu Huo; Jianna Liu; Xianjing Hong; Haochen Bai; Zongling Chen; Jinming Che; Hailin Yang; Yanjun Tong; Shoushuai Feng (Bioresource Technology, 2024)

Tetraploid induction identification and transcriptome preliminary analysis of black currant (Ribes rubrum L.) - Ruiquan Dong; Yi Pei; Lingyan Hong; Jiangli Nie; Yuhang Chen; Huili Yan; Yanjun Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Cobalt induces neurodegeneration through FTO-triggered autophagy impairment by targeting TSC1 in an m6A-YTHDF2-dependent manner - Jianping Tang; Fuli Zheng; Xu Liu; Yanjun Li; Zhenkun Guo; Xinpei Lin; Jinfu Zhou; Yu Zhang; Guangxia Yu; Hong Hu; Wenya Shao; Siying Wu; et al. (Journal of Hazardous Materials, 2023)

Does forest farm carbon sink projects affect agricultural development? Evidence from a Quasi-experiment in China - Jian Liu; Yanjun Ren; Yu Hong; Thomas Glauben (Journal of Environmental Management, 2023)

Seasonal evolution of aerosol loading and its vertical distribution in northeastern China from long-term satellite observations and model reanalysis - Hujia Zhao; Ke Gui; Yanjun Ma; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Lei Zhang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2023)

An approach for dynamic stress-free perception of goose body mass - Yanjun Zhang; Jiawen Han; Hong Miao; Shanwen Zhang; Daoqing Gong (Biosystems Engineering, 2023)

Formation and evolution of secondary particulate matter during heavy haze pollution episodes in winter in a severe cold climate region of Northeast China - Ye Hong; Junying Sun; Yanjun Ma; Yangfeng Wang; Xiaolan Li; Yunhai Zhang; Ningwei Liu; Deping Zhou (Environmental Science and Pollution Research, 2022)

Incineration experiment of medical waste of novel coronavirus pneumonia (COVID-19) in a mobile animal carcass incinerator - Shaorui Zhang; Yanjun Zhang; Fengjun Wang; Da Kang; Jingjie Wang; Minghao Wang; Chunwei Zhang; Yongtang Wang; Hong Liu; Baodong Zhou; Yong Wu (Waste Disposal & Sustainable Energy, 2021)

The treatment and follow‐up of ‘recurrence’ with discharged COVID ‐19 patients: data from Guizhou, China - Maolu Tian; Yanjun Long; Yang Hong; Xiangyan Zhang; Yan Zha (Environmental Microbiology, 2020)
Summary We reported 20 cases of discharged COVID‐19 patients whose RT‐PCR test results showed ‘re‐positive’. After finding ‘re‐positive’, these patients were admitted to hospital for the second time and were followed up until the end of May 2020. We recorded detailed treatment and follow‐up process, and collected relevant data. The possible causes and potential clinical significance of this phenomenon are discussed.

Tropical cyclone damages in Mainland China over 2005–2016: losses analysis and implications - Hong Wang; Min Xu; Anselem Onyejuruwa; Yanjun Wang; Shanshan Wen; Andrew E. Gao; Yubin Li (Environment, Development and Sustainability, 2019)

Application of Avaatech X-ray fluorescence core-scanning in Sr/Ca analysis of speleothems - Dong Li; Liangcheng Tan; Fei Guo; Yanjun Cai; Youbin Sun; Gang Xue; Xing Cheng; Hong Yan; Hai Cheng; R. Lawrence Edwards; Yongli Gao; Jessica Kelley (Science China Earth Sciences, 2019)

Using trace elements of magnetite to constrain the origin of the Pingchuan hydrothermal low-Ti magnetite deposit in the Panxi area, SW China - Yanjun Wang; Weiguang Zhu; Hong Zhong; Zhongjie Bai; Junhua Yao; Chong Xu (Acta Geochimica, 2019)

Rural solid waste—characteristics and leachate pollution assessment for different precipitation levels, China - Huiyuan Yang; Bo Yue; Yanjun Liu; Xiaohui Wu; Hong Gao; Zhibin Zhang; Zhuoyi Yan (Environmental Science and Pollution Research, 2019)

Water-soluble ion components of PM10 during the winter-spring season in a typical polluted city in Northeast China - Ye Hong; Yanjun Ma; Junying Sun; Chaoliu Li; Yunhai Zhang; Xiaolan Li; Deping Zhou; Yangfeng Wang; Ningwei Liu (Environmental Science and Pollution Research, 2019)

Clinical evaluation of a panel of multiplex quantitative real-time reverse transcription polymerase chain reaction assays for the detection of 16 respiratory viruses associated with community-acquired pneumonia - Dan Zhang; Haiyan Mao; Xiuyu Lou; Junhang Pan; Hao Yan; Hongfeng Tang; Yan Shu; Yun Zhao; Xiaoli Cheng; Hong Tao; Yanjun Zhang; Xuejun Ma (Archives of Virology, 2018)

Comparison of Two Air Pollution Episodes over Northeast China in Winter 2016/17 Using Ground-Based Lidar - Yanjun Ma; Hujia Zhao; Yunsheng Dong; Huizheng Che; Xiaoxiao Li; Ye Hong; Xiaolan Li; Hongbin Yang; Yuche Liu; Yangfeng Wang; Ningwei Liu; Cuiyan Sun (Journal of Meteorological Research, 2018)

HOTAIR functions as a competing endogenous RNA to regulate PTEN expression by inhibiting miR-19 in cardiac hypertrophy - Yanjun Lai; Shuai He; Liming Ma; Hong Lin; Biyun Ren; Jing Ma; Xinyu Zhu; Shifang Zhuang (Molecular and Cellular Biochemistry, 2017)

The response and detoxification strategies of three freshwater phytoplankton species, Aphanizomenon flos-aquae, Pediastrum simplex, and Synedra acus, to cadmium - Xiaofei Ran; Hong Yue; Xiaoli Fu; Yuanhao Kang; Sha Xu; Yanjun Yang; Jinzhu Xu; Junqiong Shi; Zhongxing Wu (Environmental Science and Pollution Research, 2015)

Co-expression of Oct-4 and Nestin in human breast cancers - Caigang Liu; Xuezhao Cao; Yanjun Zhang; Hong Xu; Ruishan Zhang; Yunfei Wu; Ping Lu; Feng Jin (Molecular Biology Reports, 2012)

Long-Term Heavy Metal Pollution and Mortality in a Chinese Population: An Ecologic Study - Mao Wang; Yanjun Xu; Shangxia Pan; Jinxin Zhang; Aiming Zhong; Hong Song; Wenhua Ling (Biological Trace Element Research, 2011)

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago - Xiaoke Qiang; Zhisheng An; Yougui Song; Hong Chang; Youbin Sun; Weiguo Liu; Hong Ao; Jibao Dong; Chaofeng Fu; Feng Wu; Fengyan Lu; Yanjun Cai; et al. (Science China Earth Sciences, 2011)